2021
DOI: 10.1177/03611981211049109
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities and Limitations of Telematics for Vehicle Emissions Inventories

Abstract: Eastern Research Group, Inc. evaluated the current state of personal vehicle telematics data with respect to emission inventory development, identifying relative strengths and weaknesses, and how these data could align better with the needs of emission modelers. A market survey of telematics firms provided an overview of available data, and identified several candidate sources for location-based and engine-based telematics data on personal vehicles. Data were then purchased from three different vendors: Street… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…21,22 The mode diameter found in this study is also close to recent findings that reported the mode diameter of ∼1.4 μm from disc brakes at temperature below 100 °C. 5,38 In this study, the mode diameter stayed at the low end of previous findings potentially because the temperature of the HD drum brakes was generally lower than the disc brakes in previous studies.…”
Section: ■ Materials and Methodssupporting
confidence: 39%
See 2 more Smart Citations
“…21,22 The mode diameter found in this study is also close to recent findings that reported the mode diameter of ∼1.4 μm from disc brakes at temperature below 100 °C. 5,38 In this study, the mode diameter stayed at the low end of previous findings potentially because the temperature of the HD drum brakes was generally lower than the disc brakes in previous studies.…”
Section: ■ Materials and Methodssupporting
confidence: 39%
“…45 A more recent study showed that brake-wear PM emissions are not necessarily at a similar level between the front and rear brakes of HD vehicles. 5 This study is limited to a proof-of-concept by demonstrating brake-wear PM emission measurements from a single brake of each test vehicle that was simulated on a two-wheel chassis dynamometer. For that reason, it was difficult to extrapolate the emissions data collected from a single brake into the total brake-wear PM emissions of HD vehicles in this study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This project did not estimate the monetary value of the data tools provided to the advocates. As previously mentioned, licenses for some emerging data software tools can be very expensive (Koupal et al, 2022;Nelson et al, 2021;Lee and Sener, 2020; it should be noted that Strava made their Metro platform free halfway into the MDSS program term). In this pilot program, the project sponsors bore the cost.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…With the emergence of big mobility data, increasingly used by local governments to aid in transportation planning (Englin and Davis, 2021;Yang, Cetin and Ma, 2020), lack of access to the same data may inhibit advocates from contributing to planning. Subscriptions to emerging mobility data tools can be prohibitively expensive for cities (Koupal et al, 2022;Nelson et al, 2021;Lee and Sener, 2020), let alone not-for-profit advocacy groups. Working with emerging mobility data often requires a high level of data science skills (Nelson et al, 2021), which may limit the degree to which advocates could use the tools even if they had access.…”
Section: Introductionmentioning
confidence: 99%